Optimal physicochemical properties of dried litchis for Thai consumers - Precoppe, Marcelo; Nagle, Marcus; Mahayothee, Busarakorn; Udomkun, Patchimaporn; Janjai, Serm; Müller, Joachim (International Journal of Agricultural and Biological Engineering, 2014)
The litchi is a fruit essential for the economies of several Southeast Asian countries, but markets regularly reject it, mainly due to spoilage. Drying extends the shelf-life of litchis, but in Thailand the optimal characteristics of the dried product have not yet been determined. The purpose of this study was to determine the optimum physicochemical properties of dried litchis – those suitable for Thai consumers. The dried fruits were submitted to physicochemical measurement and consumer evaluation, with datasets subsequently integrated using circular ideal-point regression analysis. Response surface methodology was then used to predict the optimum physicochemical properties of the fruits. It was found that Thai consumer preferences with regard to dried litchis are for the fruits to be of golden-yellow color (L* ranging around 54; H ranging around 79°), to have a soft flesh (SMF ranging between 13 and 14 kN/100 g) and to have a sweet taste (TSS:TA ranging between 25 and 28). The results may be used in the future to prescribe pretreatments and drying conditions. Keywords: consumer preference, response surface methodology, circular ideal-point regression, product optimization, market acceptance, lychee DOI: 10.3965/j.ijabe.20140705.011 Citation: Precoppe M, Nagle M, Mahayothee B, Udomkun P, Janjai S, Müller J. Optimal physicochemical properties of dried litchis for Thai consumers. Int J Agric & Biol Eng, 2014; 7(5): 103－110.